2011
DOI: 10.1038/sj.bjc.6606055
|View full text |Cite
|
Sign up to set email alerts
|

The expression and prognostic impact of CXC-chemokines in stage II and III colorectal cancer epithelial and stromal tissue

Abstract: Background:The CXC-chemokine expression is linked with colorectal cancer (CRC) progression but their significance in resected CRC is unclear. We explored the prognostic impact of such expression in stage II and III CRC.Methods:Tissue microarrays were constructed from stage II and III CRC biopsies (n=254), and the expression of CXCL1 and CXCL8, and their receptors CXCR1 and CXCR2, in malignant and adjacent normal tissue was graded by immunohistochemistry and was correlated with prognostic factors.Results:Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 43 publications
4
55
0
1
Order By: Relevance
“…In addition to the previously identified 47 integrin-MADCAM1 axis, this study revealed a number of interesting targets for antiadhesion therapy, including PECAM1, CXCL8, and CCL20, suggesting that anti-TNF-α therapy may work, at least in part, by downregulating certain CAMs [179] . Upregulation of CXCL1, CXCR1 and CXCR2 was reported by Oladipo et al [180] in tumor epithelium compared to normal adjacent tissue collected from patients with stage Ⅱ and Ⅲ CRC. In their analysis, no overall association between CXCL1, CXCR1 or CXCR2 expression and prognostic endpoints was found, although survival analysis demonstrated an inverse association between CXCL1 and recurrence-free survival in stage Ⅲ patients.…”
Section: Small and Large Intestinementioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the previously identified 47 integrin-MADCAM1 axis, this study revealed a number of interesting targets for antiadhesion therapy, including PECAM1, CXCL8, and CCL20, suggesting that anti-TNF-α therapy may work, at least in part, by downregulating certain CAMs [179] . Upregulation of CXCL1, CXCR1 and CXCR2 was reported by Oladipo et al [180] in tumor epithelium compared to normal adjacent tissue collected from patients with stage Ⅱ and Ⅲ CRC. In their analysis, no overall association between CXCL1, CXCR1 or CXCR2 expression and prognostic endpoints was found, although survival analysis demonstrated an inverse association between CXCL1 and recurrence-free survival in stage Ⅲ patients.…”
Section: Small and Large Intestinementioning
confidence: 99%
“…In their analysis, no overall association between CXCL1, CXCR1 or CXCR2 expression and prognostic endpoints was found, although survival analysis demonstrated an inverse association between CXCL1 and recurrence-free survival in stage Ⅲ patients. Interestingly, CXCL8 positivity in the tumor infiltrate correlated with earlier disease stage and improved relapse-free survival in multivariate Cox regression analysis [180] . Schroepf et al [181] screened samples collected from 501 German patients with IBD (336 CD, 165 UC) including 258 children and 243 adults as well as 231 controls.…”
Section: Small and Large Intestinementioning
confidence: 99%
See 2 more Smart Citations
“…More than half a million people in the world annually are victims of it (Oladipo et al, 2011;Peddareddigari et al, 2010). This is also the third most common cancer among Asian men and women and its prevalence is increasing (Pourhoseingholi, 2012).…”
Section: Introductionmentioning
confidence: 99%